The Influence of Price, Product Quality and Promotion on Purchasing Decisions at UD Kerupuk Rambak Lestari Eco Tulungagung: Pengaruh Harga, Kualitas Produk dan Promosi Terhadap Keputusan Pembelian Pada UD Kerupuk Rambak Lestari Eco Tulungagung - Putri Firnanda, Titania; Saptaria, Lina (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
The study aims to assess how price, product quality, and promotion affect purchase decisions on Lestari Eco Tulungagung. Primary data are gathered through questionnaire distribution, supplemented by secondary data from a literature review. The population consists of all consumers of Lestari Eco Tulungagung, with a sample of 100 respondents selected employing the Accidental Sampling method. Employing a quantitative approach, the research utilizes data analysis methods including instrument testing, classical assumptions, and hypothesis testing. Analysis conducted using SPSS version 27 indicates that both collectively and individually, price, product quality, and promotion significantly impact purchase decisions on Lestari Eco Tulungagung.